Persistence of Multimorbidity Among Women Aged 15–49 Years in India: An Analysis of Prevalence, Patterns and Correlation - Hossain, Babul; Govil, Dipti; Sk, Md Illias K. (International Journal of Public Health, 2021)
Specific knowledge of the coexisting combinations of morbidities viz. anaemia, hypertension, high glucose level and overweight for women aged 15-49 years are missing despite knowing women’s higher share in multimorbidity in higher ages. The present study has examined the patterns and possible correlates of coexisting morbidities among women aged 15-49 years based on biomarker measurement data at the national level in India. The study used the data from the fourth round of the National Family Health Survey (NFHS) conducted during 2015-16 for 656,080 women aged 15 to 49 years. Simple disease count approach was used to calculate the number of morbidities coexisting in women. Multinomial logistic regression was applied to analyse the predictors of multimorbidity among women. Almost 30 % of the women had any of the selected morbidity and 9% of them had two or more morbidities. Hypertension and overweight combination (3%) was the most prevalent among women. The risk of having two or more morbidities was predominantly high among women aged above 30 years, low educated women, women from the wealthier group, ever-married women and women who were consuming tobacco as compared to their counterparts. From the policy perspective, the identification of groups of women vulnerable to multimorbidity will help in the selection of programmatic focus and preventive public health intervention in adult phase to reduce the multimorbidity burden among women in old ages.